(3LhGeY GdMSGH HGdJNJ hGdJQGHs ((3eMehO Hf eSYhO Hf GdeUdM (B[(3GdTjQGRi(B] (3GdeJWjH s)
(3ChdgG (B:s
(3hHYO, agPG eNJUQ ai PcQ GdCYeGd GdJi jMJGL EdjgG GdMSGH hgh eQJH ai aUhd JTJed s
(3BNQgG (B:s
(3adG fWhd GdcdGe HEjQGO CeKdJgG s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B39 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B611s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdQjGVjGJs